Mengawal Tumbuh Kembang Balita dengan Optimalisasi Stimulasi Perkembangan Masa Usia Dini di Masa Pandemi Covid-19 - Dian Furwasyih; Dewi Susilawati; Rahmayeni Supri; Reca Yolandha (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Monitoring of growth and development is an activity to detect early growth irregularities (malnutrition or poor nutritional status, short children), developmental deviations (late speaking), and mental emotional disorders (impaired concentration and hyperactivity). The rapid growth and development in the first 1,000 days of life makes monitoring of child development very important at this age. The first 1,000 days of life are counted from the time of conception in the mother's womb until the child is 2 years old. In children aged 2 years, the height has reached half of the adult's height and the brain development has reached 80% of the adult brain. Since March 2020, Indonesia has been hit by the COVID-19 pandemic. This resulted in the temporary suspension of posyandu activities in various regions in Indonesia. Fears of a pandemic condition make parents afraid to bring toddlers to clinics and puskesmas. One of the easiest steps for mothers and caregivers to take to stimulate the growth and development of toddlers at home is baby massage. Solutions and targets The outputs offered in this activity are growth and development stimulation education, infant massage demonstrations, and assistance to mothers of toddlers for infant massage for 2x a month. The output targets are publication of articles in the journal Community Service, print media publications, and increasing community empowerment and strengthening knowledge and developing community habits in healthy behavior